Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2002
DOI: 10.1046/j.1440-1711.2002.01107.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunity to asexual blood stage malaria and vaccine approaches

Abstract: SummaryThe development of a malaria vaccine seems to be a definite possibility despite the fact that even individuals with a life time of endemic exposure do not develop sterile immunity. An effective malaria vaccine would be invaluable in preventing malaria-associated deaths in endemic areas, especially amongst children less than 5 years of age and pregnant women. This review discusses our current understanding of immunity against the asexual blood stage of malaria -the stage that is responsible for the sympt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
71
0
7

Year Published

2005
2005
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(81 citation statements)
references
References 159 publications
3
71
0
7
Order By: Relevance
“…A strong innate immune response is important in early bloodstage malaria infection to prevent the parasite from entering human red blood cells and cause disease, while strong adaptive immune responses may protect against malaria by inhibiting merozoite invasion of erythrocytes as well as enhance clearance of infected erythrocytes from the circulation. 53,54 The mechanism by which rBCG induces more inflammatory response than parental BCG and LPS is not yet known. A previous report showed that glycosylphosphatidylinositol (GPI) anchors of merozoite membrane proteins released from rupturing malaria-infected erythrocytes capable to induce low levels of TNF-α production in macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…A strong innate immune response is important in early bloodstage malaria infection to prevent the parasite from entering human red blood cells and cause disease, while strong adaptive immune responses may protect against malaria by inhibiting merozoite invasion of erythrocytes as well as enhance clearance of infected erythrocytes from the circulation. 53,54 The mechanism by which rBCG induces more inflammatory response than parental BCG and LPS is not yet known. A previous report showed that glycosylphosphatidylinositol (GPI) anchors of merozoite membrane proteins released from rupturing malaria-infected erythrocytes capable to induce low levels of TNF-α production in macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…Anti-Plasmodium antibodies can prevent merozoites of infecting new red blood cells (RBCs), block cytoadherence to endotheliar capillary of infected RBCs (iRBCs), and promote phagocytosis by mononuclear cells [16,23,24]. However, persistence of significant levels of antimalarial antibodies relies on the continuous challenge resulting of chronic exposition to infection [3], probably as consequence of the impaired establishment of B cell memory [19].…”
Section: Introductionmentioning
confidence: 99%
“…Antibodies are believed to be an important component of acquired protective immunity, in addition to other factors (2). During blood-stage replication, P. falciparum merozoites invade erythrocytes, and antibodies that inhibit invasion and subsequent replication are believed to be important in mediating both acquired immunity and immunity generated by candidate blood-stage vaccines (3)(4)(5). However, the targets of acquired inhibitory antibodies are largely undefined.…”
Section: Introductionmentioning
confidence: 99%